Causal factors influencing the development of leadership potential in sports organizations - Praphuntha, Nalineewan; Unarmat, Arthicha; Thanaiudompat, Thanarit (Edelweiss Applied Science and Technology, 2026)
This research aimed to examine the relationships between leadership factors affecting the development of leadership potential in sports organizations. The study employed a quantitative research design with a sample of 200 sports organization leaders from Chonburi Province, selected through simple random sampling. The research instruments consisted of questionnaires measuring leadership potential development in sports organizations, technological literacy, team leadership, and flexibility and adaptability. Data were analyzed using stepwise multiple regression. The findings revealed that: 1) All three leadership potential factors were significantly correlated with the development of leadership potential in sports organizations at the .05 significance level, with a multiple correlation coefficient of 0.324, indicating that these three factors accounted for 32.40% of the variance in leadership potential development in sports organizations. 2) All three factors significantly influenced the development of leadership potential in sports organizations at the .05 significance level, with standardized regression weights of 0.374, 0.372, and 0.351, respectively. This factor serves as a critical form of organizational immunity, enabling leaders to navigate volatile environments by pivoting business models away from traditional revenue streams toward digital innovation. Furthermore, technological utilization potential is established as a vital differentiator for data-driven decision-making, while sports team building acts as the human capital foundation necessary for aligning diverse talents toward a unified vision. Ultimately, effective sports organizational team leadership in the modern era is defined by the ability to bridge high-tech data proficiency with high-touch interpersonal cohesion to ensure long-term institutional sustainability and stakeholder confidence.